On-campus promoting health literacy and behavior in adolescent athletes: A pilot study - Meng-Che Tsai (Social Health and Behavior, 2018)
Introduction: Little is known about the profile of health-promoting behaviors in Taiwanese adolescent athletes. We codesigned a school-based extracurricular club with the adolescent athletes and aimed to examine the effect of program on the health-promoting behaviors among the participants. Methods: We recruited a sample of 40 athlete students: 20 participants from the health promotion club (intervention group) and 20 comparisons from other extracurricular clubs (control group). The content of health promotion program contained a wide array of health issues, such as growth, nutrition, sport injury, and life resuscitation. Certified physicians and physiotherapists provided lectures, workshops of experimentation, and forums of group discussion. We compared the health-promoting behaviors based on the Adolescent Health Promotion (AHP) scale before and after the program and between the intervention and control groups. Results: Athlete students scored higher in exercise (20.9 ± 3.6 vs. 16.3 ± 3.7, P < 0.01) but lower in nutrition (19.7 ± 3.4 vs. 22.1 ± 3.9, P < 0.01) among the AHP scale items than general students referenced in the literature. Athletes who participated in health promotion club showed improvement in AHP scores, particularly in the domain of health responsibility that was persistent up to 6 months after the intervention. Conclusion: We identified a general lack of healthy nutrition practices in these athlete youth. After 20 weeks' training, the participants adopted healthier behaviors that persisted even longer. Further research of larger participation is needed to evaluate the effectiveness of the scheme.